2009
DOI: 10.1007/s12011-008-8307-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble Fiber Pectin on Growth and Intestinal Iron Absorption in Rats During Recovery from Iron Deficiency Anemia

Abstract: The objective of this study was to verify whether soluble fiber pectin interferes in growth and intestinal iron absorption in rats during iron deficiency anemia recovery. Twenty-one-day-old Wistar rats (n = 48) were fed for 2 weeks on a diet without iron in order to induce iron deficiency anemia. The anemic animals (age = 36 days) were divided into two groups: (1) pectin, 50 g of pectin per kilogram of diet, and (2) control, diet without dietary fiber. Iron was added to the diets for the two groups in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…It was generally believed that fibers (mostly insoluble) would have a negative effect on mineral absorption because they formed insoluble and stable complexes not absorbed by the gut [15,21,22,23]; however, prebiotics such as inulin and oligofructose are extensively studied in calcium absorption and contradict this principle. The mechanism involved is that the soluble fiber reaches the colon intact and undergoes colonic microbiota fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…It was generally believed that fibers (mostly insoluble) would have a negative effect on mineral absorption because they formed insoluble and stable complexes not absorbed by the gut [15,21,22,23]; however, prebiotics such as inulin and oligofructose are extensively studied in calcium absorption and contradict this principle. The mechanism involved is that the soluble fiber reaches the colon intact and undergoes colonic microbiota fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse reactions in the postoperative digestive system that had not been fully restored were avoided as much as possible; the incidence rate of adverse reactions in the study group was 6.77% and 14-32% in the control group (P < 0.05). Nutrison was gradually introduced as the dietary fibers it contains play a key role in promoting intestinal recovery (Feltrin et al, 2009). On the first day after surgery, albumin and prealbumin levels in the two groups decreased.…”
Section: Comparison Of Changes In Inflammatory Reaction Indicators Bementioning
confidence: 99%
“…Martino et al, (2011), observed no effect of dietary fiber of hull soybean on iron bioavailability. However, other studies have pointed out that anemic animals fed soluble fiber showed recovery of hemoglobin similar to that of the control group; in those studies, ferrous sulfate was used as the control diet (De Cássia Freitas et al, 2006;Feltrin et al, 2009). The lack of consensus among various studies is due to experimental conditions such as short-term or long-term consumption of the food test, experimental models, the food matrix, and the age and/or nutritional/physiologic status of the animals (Lobo et al, 2007(Lobo et al, , 2011Scholz-Ahrens & Schrezenmeir, 2007).…”
Section: Discussionmentioning
confidence: 99%